2009
DOI: 10.1161/circgenetics.108.785659
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Function in Hypertension

Abstract: Background-Hypertension is a complex trait, with deranged autonomic control of circulation. Chromogranin B (CHGB) is the most abundant core protein in human catecholamine secretory vesicles, playing an important role in their biogenesis. Does common interindividual variation at the CHGB locus contribute to phenotypic variation in CHGB and catecholamine secretion, autonomic stability of circulation, or blood pressure (BP) in the population? Methods and Results-To probe interindividual variability in CHGB, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…CHGB knockout mice were generated from mouse embryonic stem cells by homologous recombination, as previously described ( 18,22 ). The effect of CHGB knockout on dense-core secretory granule abundance was examined by transmission electron microscopy (EM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHGB knockout mice were generated from mouse embryonic stem cells by homologous recombination, as previously described ( 18,22 ). The effect of CHGB knockout on dense-core secretory granule abundance was examined by transmission electron microscopy (EM).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore CHGB gives rise to early, pathogenic “intermediate phenotypes” ( 17 ) for exploration of sympathoadrenal activity in human essential hypertension. Indeed, we reported that two common CHGB promoter SNPs, A-296C (rs236140) and A-261T (rs236141), are strongly associated with hypertension in the population ( 18,19 ), while in CHGB knockout ( CHGB[ −/−]) mice, we observed substantial elevations in both SBP and DBP ( 18 ). In this report, we have studied how CHGB quantitative variation (both over- and under-expression) affects not only secretory granulogenesis, but also catecholamine uptake, storage, and exocytotic release.…”
Section: Introductionmentioning
confidence: 99%
“…Several functions have been proposed for CgB, including the following: granule biogenesis and sorting (Natori and Huttner, 1996;Huh et al, 2003), Ca 2ϩ sequestration and release (Yoo and Jeon, 2000), and a source of bioactive peptides (Strub et al, 1995;Winkler et al, 1998;Taupenot et al, 2003). Chromogranin B has recently grown in importance after the unexpected finding associating it with some classes of human diseases, such as schizophrenia (Landén et al, 1999;Marksteiner et al, 2000), Alzheimer's disease (Marksteiner et al, 2000), and hypertension (Zhang et al, 2009), as well as for its possible involvement in diabetes, which has been observed in mice (Obermüller et al, submitted).…”
Section: Introductionmentioning
confidence: 99%
“…Including the previously reported phospho-variant rs910122,31 different genetic effects of CHGB variants on the risk of schizophrenia were also observed depending on sex in this study (Table 2). Furthermore, considering that CHGB rs236141 with a nominal association with schizophrenia ( p =0.05 and OR=0.63 in male subjects) has been found to be a gender-specific marker for blood pressure disease, 39 our findings suggest that CHGB could be a gender-specific marker for schizophrenia development.…”
Section: Discussionmentioning
confidence: 49%